2001
DOI: 10.1074/jbc.m005088200
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative Effects of Insulin-like Growth Factor-binding Protein-3 in Mesenchymal Chondrogenic Cell Line RCJ3.1C5.18

Abstract: Chondrogenesis results from a complex equilibrium between chondrocyte proliferation and differentiation. Insulin-like growth factors (IGFs) have a crucial role in chondrogenesis, but their mechanisms of action are not well defined. IGF-binding protein-3 (IGFBP-3) is the major carrier for circulating IGFs in postnatal life, and has been shown to have IGF-independent effects on proliferation of several cancer cell lines. In this study, we have evaluated the IGF-independent and -dependent effects of IGFBP-3 on ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
78
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(79 citation statements)
references
References 46 publications
1
78
0
Order By: Relevance
“…We then differentiated C5.18 cells for an extended time course toward terminally differentiated hypertrophic-like chondrocytes. 18 Differentiation of these cells was confirmed by increased gene expression of chondrocyte markers Acan, Col2a1, Col10a1, and Alpl as well as nodule formation and glycosaminoglycan production ( Fig. S1A-H).…”
Section: Pharmacological Inhibitors Of Lysosomal Activity Stimulated mentioning
confidence: 77%
“…We then differentiated C5.18 cells for an extended time course toward terminally differentiated hypertrophic-like chondrocytes. 18 Differentiation of these cells was confirmed by increased gene expression of chondrocyte markers Acan, Col2a1, Col10a1, and Alpl as well as nodule formation and glycosaminoglycan production ( Fig. S1A-H).…”
Section: Pharmacological Inhibitors Of Lysosomal Activity Stimulated mentioning
confidence: 77%
“…RCJ3·1C5·18 cells are derived from rat calvaria mesenchymal cells and over 2 weeks of culture, without requiring biochemical and oncogenic transformation, they sequentially differentiate from MCCs to terminally differentiated chondrocytes in a highly predictable and reproducible manner (Grigoriadis et al 1996, Lunstrum et al 1999, Spagnoli et al 2001. Furthermore, RCJ3·1C5·18 cells do not express IGFs or IGFBP-3, so the action of these peptides can be studied without interference from endogenous proteins (Spagnoli et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Using RCJ3·1C5·18 chondrogenic cells as an established model to study MCC fate during the chondrogenesis process in vitro, we have previously reported that: IGFBP-3 has IGF-independent antiproliferative and apoptotic effects in MCCs; the IGFBP-3 apoptotic effect in MCCs requires STAT-1 expression and activation; and IGFBP-3 modulates the chondrocytic differentiation rate by regulating MCC growth (Spagnoli et al 2001, Longobardi et al 2003. RCJ3·1C5·18 cells are derived from rat calvaria mesenchymal cells and over 2 weeks of culture, without requiring biochemical and oncogenic transformation, they sequentially differentiate from MCCs to terminally differentiated chondrocytes in a highly predictable and reproducible manner (Grigoriadis et al 1996, Lunstrum et al 1999, Spagnoli et al 2001. Furthermore, RCJ3·1C5·18 cells do not express IGFs or IGFBP-3, so the action of these peptides can be studied without interference from endogenous proteins (Spagnoli et al 2001).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations